Research on the effect of professional competency of college physical education teachers on students’ motivation for physical education learning - Luo, Wanhong; Sun, Xu; Zhou, Zongkai; Tian, Zuguo; Chen, Zichao (Frontiers in Psychology, 2025)
IntroductionThis study, based on self-determination theory, constructs a multilevel model to examine the impact of the professional competency of college physical education teachers (PCCPET) on students’ motivation for physical education learning (SMPEL).MethodsUsing sample data from 533 university students, structural equation modeling was applied to explore the influence of physical education teachers’ professional competency on students’ motivation.ResultsThe results indicate that the professional competency of college physical education teachers (PCCPET) has a significant positive effect on students’ motivation for physical education learning (SMPEL). Additionally, teacher professional competency indirectly affects students’ motivation through satisfying students’ psychological needs satisfaction for physical education learning (PNSPEL), and this mediating effect is statistically significant. Finally, gender plays a significant moderating role between the professional competency of college physical education teachers (PCCPET) and students’ motivation for physical education learning (SMPEL), with female students being more positively influenced by teacher professional competency.DiscussionTherefore, in future teaching practices, efforts should be made to enhance the professional competency of physical education teachers and ensure that teachers provide tailored instruction based on students’ gender to effectively stimulate students’ motivation for physical education learning.